Big five personality traits as a catalyst for instructional competency: A scoping review in educational leadership - Erna Suwardi; Muhamad Suhaimi Taat; Roslee Talip; Mohd Sobrye Paimin (RSIS International, 2025)
Leadership competencies are becoming increasingly critical in education, particularly as institutions respond to shifting pedagogical paradigms and complex learning environments. While various leadership styles have been widely examined, the role of individual personality traits, specifically the Big Five Personality Traits (B5PT), in shaping instructional competency remains underexplored. This scoping review systematically maps empirical studies from 2020 to 2025 that investigate the influence of B5PT on instructional competency in educational contexts. Guided by Arksey and O’Malley’s six-stage framework, relevant literature was sourced from Scopus, Web of Science (WoS), and ERIC databases. Traits such as conscientiousness and emotional stability were consistently associated with effective instructional competency. However, findings on openness were mixed, with some studies linking it to pedagogical innovation and risk-taking, while others reported non-significant or even negative associations with instructional outcomes. Thematic analysis revealed four overarching domains of influence: work empowerment, attitude, behaviour, and management support. These findings offer both theoretical insights and practical implications for leadership development, underscoring the potential of personality-informed strategies to enhance instructional effectiveness.